Pilgrimage and tourism to holy cities : ideological and management perspectives - Leppäkari, Maria, 1972-; Griffin, Kevin A. (CABI religious tourism and pilgrimage series, 2017)
This book covers the ideological motives and religious perceptions behind travel to sites prescribed with sanctity in Judaism, Christianity and Islam, and puts emphasis on a practical application of religious tourism and pilgrimage management. Part I of the book, 'Western Pilgrimage to Holy Cities in Judaism, Christianity and Islam', provides historical and contemporary perspectives of pilgrimage across these religions. Part II, 'Managing Pilgrimage Sites in Holy Cities', addresses a range of management issues such as logistics, infrastructure, and malevolent visitor behaviour. The book has 13 chapters, and includes a list of discussion points and a subject index.